Field effect transistors (Minnesota : Video Training Resource [production company] : Virginia : Coastal Skills Training [distributor], 1987)
Introduces to the field effect transistors and focuses on the characteristics and operation of junction FETs and describes how they differ from bipolar transistors
Copy available in DVD format
Keywords: Field-effect transistors; Transistors circuits